Neutrophil extracellular trap-microparticle complexes trigger neutrophil recruitment via high-mobility group protein 1 (HMGB1)-toll-like receptors(TLR2)/TLR4 signalling - Wang, Yongzhi; Du, Feifei; Hawez, Avin ; 0000-0001-7391-7379; Mörgelin, Matthias; Thorlacius, Henrik (British Journal of Pharmacology, 2019)
Background and Purpose: Recent data suggest that neutrophil extracellular traps (NETs) form aggregates with microparticles (MPs) upon activation of neutrophils although the functional role of NET-MP complexes remain elusive. The objective of this study was to examine the role of NET-MP aggregates in leukocyte recruitment in vivo. Experimental Approach: PMA stimulation of murine bone marrow neutrophils generated NET-MP complexes and pretreatment with caspase and calpain inhibitors resulted in the formation of NETs depleted of MPs. Leukocyte–endothelium interactions were studied by using intravital microscopy of the mouse cremaster microcirculation. Key Results: Intrascrotal injection of NET-MP aggregates dose-dependently increased leukocyte recruitment. In contrast, leukocyte responses were markedly reduced after administration of NETs depleted of MPs. Neutrophil depletion abolished intravascular and extravascular leukocytes in response to challenge with NET-MP complexes. Electron microscopy revealed that NET-associated MPs express HMGB1. Notably, immunoneutralization of HMGB1 markedly decreased NET-MP complex-induced neutrophil accumulation. Moreover, inhibition of TLR2 and TLR4 significantly reduced neutrophil recruitment in response to NET-MP aggregates. Conclusions and Implications: These data show that NET-MP complexes are potent inducers of neutrophil recruitment, which is dependent on HMGB1 expressed on MPs and mediated via TLR2 and TLR4. Blocking MP binding to NETs or downstream inhibition of the HMGB1-TLR2/TLR4 axis might provide useful targets to attenuating NET-dependent tissue damage in acute inflammation.